ChemInform Abstract: Cobalt‐Catalyzed Direct Amination of Arenes with Alkylamines via Bidentate‐Chelation Assistance. Issue 52 (6th December 2016) - Yan, Qiangqiang; Xiao, Tangxin; Liu, Zhanxiang; Zhang, Yuhong
Abstract: The title reaction features low catalyst loading and readily available reagents, but it only applies to cyclic amines.